Intermediate-term outcomes after aortic valve replacement with a novel RESILIATM tissue bioprosthesis - Bartus, Krzysztof; Litwinowicz, Radoslaw; Bilewska, Agata; Stapor, Maciej; Bochenek, Maciej; Rozanski, Jacek; Sadowski, Jerzy; Filip, Grzegorz; Kapelak, Boguslaw; Kusmierczyk, Mariusz (Journal of Thoracic Disease, 2019)
Background: The durability of bioprosthetic heart valves is limited by structural valve deterioration (SVD) due to long-term calcification. A novel bioprosthetic tissue (RESILIATM) has been developed which, in preclinical studies, has shown reduced calcification. The purpose of this study was to evaluate the intermediate-term clinical outcomes and hemodynamic performance of this tissue. Methods: A prospective, single-arm, observational trial was conducted in patients who required surgical aortic valve replacement (AVR). Between July 2011 and February 2013, 133 patients were implanted at two sites in Poland. Hemodynamic performance and clinical outcomes were assessed annually through 4 years of follow-up. All safety events were adjudicated by an independent Clinical Events Committee, and echocardiographic data were evaluated by a core laboratory. Results: Patients were 65.3±13.5 years old and 26% were ≤60 years old. The average follow-up was 3.8±1.1 (median: 4.1; IQR, 4.0–4.3) years. Early (≤30 day) and late (>30 day) all-cause mortality rates were 2.3% (n=3) and 3.2% late patient-years (n=16), respectively. There were no cases of early or late SVD. There was one early case of major paravalvular leak (0.8%), and no late cases. At 4 years, the mean gradient was 14.5± 7.4 mmHg and the effective orifice area was 1.6±0.4 cm2, both markedly improved from baseline. At 4 years, the New York Heart Association functional class had improved from baseline in 54.5% of patients. Conclusions: The aortic bioprosthesis with novel RESILIATM tissue demonstrated excellent hemodynamic performance and safety outcomes over 4 years. Longer follow-up will be important to confirm the durability of this bioprosthesis.